(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): How many serious bodily injuries occurred as a result of traffic accidents, and what kind of injuries were those in 2020? Aim: To determine how many seriously injured participants in traffic accidents were in 2020, our purpose was to determine what is the proportion of serious bodily injuries by sex, in which age group the most severe injuries occurred and what is the impact of weather on the number and severity of serious bodily injuries. Method: After reviewing the relevant literature, we used frequency statistics and chi-square tests for the data obtained from the official police website. For the quantitative method, we used an in-depth semi-structured interview with two relevant experts in the field. Results: Regarding road traffic hazards, there are differences between males and females, the youngest and oldest are most at risk in road traffic, and more severe injuries occur in nice weather. Organization: The establishment of an effective traffic safety system is possible only with the prior identification, analysis and elimination of critical causes that affect safety. Society: Greater road safety requires changes in the individual’s thinking and acting as a road user. Originality: The originality of the research lies in using a combination of quantitative and qualitative research methods. The topic is very interesting from a social point of view. Limitations/Future Research: The COVID-19 pandemic affects the results. The research should be done for a more extended period, at least ten years.